Il nuovo disordine internazionale - Ferraris, Luigi Vittorio (Rivista di studi politici internazionali, 2013)
Modern history in its continuous flow presents successive international systems: the Westphalian; the Vienna Congress, which tried unsuccessfully to thwart changes; the League of Nations failed in its endeavor for peace. After the 1945 victory a new system was introduced: a bipolar one built on the contrast between two different ideological approaches. During the ensuing Cold War it was not perceived timely that the Soviet system has started slowly to lose its grip after 1956; as a consequence of the events in 1989-1991 it looked like that the United Nations system could at last work: the Gulf War as a lonely success of multilateralism. This opened the way to the widespread engagement to export the democracy of the western brand and human rights: both should prevail universally to make peace possible. The turning point of September 11 brought to the forefront a new enemy, which declared to be against any international order or rule: the only valid response could not but be war: without taking care of the drawbacks of an uncertain collective will. However the lack of full success in Iraq and the failing results in Afghanistan sealed the failure of both unilateralism and multilateralism whilst the financial crisis shed doubts on the convenience of imposing the respect for human rights as a paramount objective, which public opinion is no longer eager to support. The responsibility or the duty to protect with the willingness to engage into armed interventions are fading away. The international system is jeopardized by the weakening of the basic principles of noninterference and integrity of the States and by the emergence of new entities which govern the world economy outside any democratic legitimacy. In such conditions it cannot be entrusted to the United Nations, which is by now irrelevant, not to Europe which is absorbed by its own problems, not fully to the United States and nevertheless without them no global strategy is conceivable. Thus the present situation is disorder, no international order because no Leviatahan is in view.Dans l’histoire moderne les systèmes internationaux se succèdent sans cesse: le système wetphalien; le Congrès de Vienne, qui n’a pas réussi a empêcher les changèments; la Société des Nations, qui n’a pas sauveguardé la paix. Après 1945 le système bipolaire a été animé par le contraste entre deux idéologies. Pendant la guerre froide on n’a pas perçu que depuis 1956 le bloc soviétique était en train de dégringoler. Comme conséquence des événements en 1989-1991 l’Onu a finalement fonctionné: la Guerre du Golfe a été un succès solitaire du multilateralisme. Cela a ouvert le chemin vers un engagement important pour exporter universallement la démocratie et les droits fondamentaux de l’homme, dans l’intérêt de la paix. Le 11 septembre a fait surgir un nouveaux ennemi, qui se déclare adversaire de n’importe quel système international: l’unique réponse valable était la guerre sans prendre garde des incertitudes de la volonté collective. Toutefois l’absence de succès en Iraq et en Afghanistan a sanctionné la faillite soit de l’unilateralisme que du multilateralisme tandis que la crise financière a mis en doute la opportunité de considérer encore les droits de l’homme comme l’objectif principal, que l’opinion publique n’est plus prête à soutenir. La responsabilité ou le devoir de protéger et la promptitude à l’intervention armée sont en train de s’effacer. D’ailleurs le système international est blessé par l’affaiblissement des principes de non ingerence et d’integrité et par le surgissement de nouvelles institutions qui gouvernent l’économie sans une claire légitimitation démocratique. Dans ces conditions il ne s’avère pas possible de confier la sauvegarde de l’ordre international à l’Onu qui est devenu inadéquat, ni à l’Europe qui se concentre sur ses propres problèmes, ni aux États Unis, sans lesquels pourtant aucune stratégie globale n’est conçevable. La situation présente signifie donc désordre sans qu’un Leviathan soit en vue.PAROLE CHIAVE: Ordine internazionale; Diritti umani; Crisi dell’unipolarismo e del multilateralismo; Società delle Nazioni; Nazioni Unite.